2022
DOI: 10.33086/nhc.v2i1.2955
|View full text |Cite
|
Sign up to set email alerts
|

Factors in the Decision to Accept the Covid-19 Vaccination: A Literature Review

Abstract: Background: The COVID-19 vaccination program was an effort made to prevent the transmission of the COVID-19 virus. Various considerations arise when this program was implemented. Individual factors are one of the factors that influence the decision to receive a COVID-19 vaccination. Objective: This literature review aims to review the factors related to the decision to receive the COVID-19 vaccination. Methods: The design used was literature review with PICO criteria (Population: General public (adult), Interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…A systematic review of 53,000 inpatients showed that 20.2% of covid-19 cases progressed to severe disease with a mortality rate of 3.1%. The risk of death will be higher in elderly people who have a history of comorbidities, such as cardiovascular disease, chronic kdney disease, and chronic obstructive pulmonary disease (6). Indonesia has not escaped the spread of this viral infection (7).…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of 53,000 inpatients showed that 20.2% of covid-19 cases progressed to severe disease with a mortality rate of 3.1%. The risk of death will be higher in elderly people who have a history of comorbidities, such as cardiovascular disease, chronic kdney disease, and chronic obstructive pulmonary disease (6). Indonesia has not escaped the spread of this viral infection (7).…”
Section: Introductionmentioning
confidence: 99%